Assessment on the distributions and exchange of anionic surfactants in the coastal environment of Peninsular Malaysia: a review - Uning, Royston; Suratman, Suhaimi; Latif, Mohd Talib; Mustaffa, Nur Ili Hamizah (Springer, 2022)
Terrestrial anionic surfactants (AS) enter the marine environment through coastal region. Despite that, in general limited knowledge is available on the coastal AS transfer pathway. This paper aims to assess the distributions and exchange of AS in the Peninsular Malaysia coastal environments, adjacent to the southern waters of South China Sea and Strait of Malacca. An assessment case study was conducted by a review on the available data from the workgroup that span between the year 2008 and 2019. The findings showed that AS dominated in the sea surface microlayer (SML, 57%) compared to subsurface water (SSW, 43 %). AS were also found to have dominated in fine mode (FM, 71 %) compared to coarse mode (CM, 29 %) atmospheric aerosols. SML AS correspond to the SSW AS (p < 0.01); however, highest enrichment factor (EF) of the SML AS was not consistent with highest SSW AS. Direct AS exchange between SML and FM and CM was not observed. Furthermore, the paper concludes AS mainly located in the SML and FM and could potentially be the main transfer pathway in the coastal environment.